Penguatan Pelayanan Keluarga Berencana pada Ibu Nifas melalui Penyuluhan dan Konseling untuk Kesejahteraan Keluarga - Sari, Lili Purnama; Irnawati, Irnawati (Universitas Pahlawan Tuanku Tambusai, 2025)
Pregnancy spacing is an important strategy in improving the quality of maternal and child health. Good family planning can reduce the risk of health complications in mothers and children. However, many postpartum mothers still do not understand the importance of proper family planning (KB) during the postpartum period. This community service activity aims to increase the understanding and motivation of postpartum mothers in choosing a contraceptive method. The method used in community service activities is carried out through education and counseling to postpartum mothers about the importance of KB for postpartum mothers, this activity also involves local midwives to provide direct assistance, so that the sustainability of KB use can be maintained in the Pattingaloang Health Center Work area. The results obtained increased understanding and awareness of postpartum mothers regarding the importance of KB during the postpartum period and increased motivation to use KB. It is hoped that there will be follow-up activities from health workers to provide health education related to health to postpartum mothers.